2019
DOI: 10.25260/ea.19.29.3.0.873
|View full text |Cite
|
Sign up to set email alerts
|

Diversidad taxonómica y funcional de aves: Diferencias entre hábitats antrópicos en un bosque subtropical

Abstract: RESUMEN.Una de las amenazas principales para la biodiversidad es el avance de las actividades humanas que implican usos extensivos de la tierra. En este estudio buscamos identificar los usos de la tierra que mejor preservan el ensamble de especies de aves y sus rasgos funcionales en un bosque subtropical. Para ello comparamos simultáneamente la diversidad taxonómica (riqueza específica y similitud en la composición de especies) y la funcional (diversidad de rasgos funcionales y similitud en la composición de r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 62 publications
3
6
0
Order By: Relevance
“…Furthermore, the forest with cattle exclusion was negatively associated with generalist species in nesting habitat selection (De la Peña, 2016). These results partially agree with what was reported by Vaccaro and Bellocq (2019) for the interior Atlantic Forest where it was observed that forest with cattle exclusion was associated with forest specialist birds, sensitive to anthropogenic disturbance, insectivorous, frugivorous, and granivorous birds. Similarly, Dardanelli et al.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, the forest with cattle exclusion was negatively associated with generalist species in nesting habitat selection (De la Peña, 2016). These results partially agree with what was reported by Vaccaro and Bellocq (2019) for the interior Atlantic Forest where it was observed that forest with cattle exclusion was associated with forest specialist birds, sensitive to anthropogenic disturbance, insectivorous, frugivorous, and granivorous birds. Similarly, Dardanelli et al.…”
Section: Discussionsupporting
confidence: 93%
“…Surprisingly, bird assemblages in the native forests (i.e., natural habitats of the Forest) were characterized by functional redundancy. These results are in accordance with those of Vaccaro and Bellocq 11 , who, for these same sites, found lower and higher functional diversity in natural habitats and tree plantations, respectively, than in other habitat types. Tree plantations exhibited functional divergence probably because they harbored not only species with traits similar to those inhabiting the native forest 57 , but also generalist species that forage and nest in a variety of environments 11 .…”
Section: Discussionsupporting
confidence: 92%
“…These results are in accordance with those of Vaccaro and Bellocq 11 , who, for these same sites, found lower and higher functional diversity in natural habitats and tree plantations, respectively, than in other habitat types. Tree plantations exhibited functional divergence probably because they harbored not only species with traits similar to those inhabiting the native forest 57 , but also generalist species that forage and nest in a variety of environments 11 . Tree plantations are generally unsuitable for native forest birds 58,59 , while extra-regional species possess traits that enable them to take advantage of the resources available not only in these habitat types but also in open habitats.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Since B. darwinii pollen presents high self‐incompatibility, the reproduction of this species strongly depends on pollinators (Vázquez & Simberloff, 2004). As occurs in other species of the genus Berberis , its fruits are consumed by birds, such as Elaenia albiceps and Turdus falcklandii (Amico & Aizen, 2005; Garcia et al, 2010), which disperse their seeds. Remarkably, its fleshy fruits are a high‐value non‐timber forest product due to its nutraceutical properties associated with a noticeable antioxidant capacity (Chamorro et al, 2019).…”
Section: Introductionmentioning
confidence: 99%